Peningkatan perilaku prososial melalui layanan bimbingan kelompok - Rasmi Dewi; Darmawansyah Darmawansyah (Universitas Indraprasta PGRI, 2022)
prosocial behavior is behavior that should be owned by students. The fact is that there are still students who show low prosocial behavior. One of the efforts to improve prosocial behavior is through group guidance services. This study aims to determine whether group guidance services are able to increase prosocial behavior in students. This research is a quantitative research with experimental type. The design used is one group pretest-posttest control group. The sample in this study amounted to 12 students drawn randomly. The research instrument used a prosocial behavior scale which amounted to 27 items. Data were analyzed using sign test. The results showed that group guidance services were effective in increasing prosocial behavior in students. It is evident that group guidance is increasingly able to be used to develop social competence in individuals.